Strategies to address COVID-19 vaccine hesitancy in First Nations peoples: a systematic review - Adeline Tinessia; Katrina Clark; Madeleine Randell; Julie Leask; Catherine King (Global Health Action)
Background First Nations peoples face disproportionate vaccine-preventable risks due to social, economic, and healthcare disparities. Additionally, during the COVID-19 pandemic, there was also mistrust and hesitancy about the COVID-19 vaccines among First Nations peoples. These are rooted in factors such as colonial histories, discriminatory medical practices, and unreliable information. Objective To examine strategies to address COVID-19 vaccine hesitancy among First Nations peoples globally. Methods A systematic review was conducted. Searches were undertaken in OVID MEDLINE, OVID EMBASE, OVID PsycINFO, CINAHL, and Informit. Searches were date limited from 2020. Items included in this review provided primary data that discussed strategies used to address COVID-19 vaccine hesitancy in First Nations peoples. Results We identified several key strategies across four countries – Australia, the USA, Canada, and Guatemala in seventeen papers. These included understanding communities’ needs, collaborating with communities, tailored messaging, addressing underlying systemic traumas and social health gaps, and early logistics planning. Conclusion The inclusion of First Nations-centred strategies to reduce COVID-19 vaccine hesitancy is essential to delivering an equitable pandemic response. Implementation of these strategies in the continued effort to vaccinate against COVID-19 and in future pandemics is integral to ensure that First Nations peoples are not disproportionately affected by disease.